Larval morphology of Atractides ildensis Tuzovskij, 2005, A. moniezi (Motaş, 1927), and A. graecus Viets, 1950 (Acari: Hydrachnidia: Hygrobatidae) - Tuzovskij, Petr V. (Zootaxa, 2012)
First illustrated descriptions of the larvae of three water mite species of the genus Atractides are presented: A. ildensis Tuzovskij, 2005, A. moniezi (Motaş, 1927), and A. graecus Viets, 1950.